Food Production or Food Aid? An African Challenge - Verheye, Willy H. (2012)
Food production is not keeping pace with Africa's rapidly growing needs. Aid programs in the 1970s and 1980s were considered a temporary solution to the most appalling famines, but Africa's food shortage appears to be worsening. This paper discusses the reasons for this situation and ways to address it. African policymakers should consider intensifying and diversifying local production and establishing systems for marketing and setting prices. Individual farmers or farmers' communities must take the initiative for the farmers while governments must take responsibility for developing and maintaining total networks.